2021
DOI: 10.1007/s11701-021-01344-y
|View full text |Cite
|
Sign up to set email alerts
|

Surgical trainee experience and opinion of robotic surgery in surgical training and vision for the future: a snapshot study of pan-specialty surgical trainees

Abstract: Background: Robotic surgery is well established across multiple surgical specialities in the United Kingdom (UK) and Republic of Ireland (ROI). We aimed to elucidate current surgical trainee experience of and attitudes to robotic surgery in a surgical training programme across the UK and ROI to determine the future role of robotic surgery in international surgical training programmes. Methods: A pan-specialty trainee cross-sectional study was performed on behalf of the Association of Surgeons in Training (ASiT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 18 publications
(25 reference statements)
0
23
0
Order By: Relevance
“…Robot-assisted surgery has gained momentum at an unprecedented pace, creating training challenges for novice surgical trainees. A recent pan-specialty trainee, cross-sectional study demonstrated that less than 12% of current surgical trainees reported having access to robotic surgery training opportunities [ 32 ]. To date, there have been numerous barriers identified for surgical trainees in accessing on-site practical robotic skills opportunities, particularly in relation to minimally invasive techniques.…”
Section: Discussionmentioning
confidence: 99%
“…Robot-assisted surgery has gained momentum at an unprecedented pace, creating training challenges for novice surgical trainees. A recent pan-specialty trainee, cross-sectional study demonstrated that less than 12% of current surgical trainees reported having access to robotic surgery training opportunities [ 32 ]. To date, there have been numerous barriers identified for surgical trainees in accessing on-site practical robotic skills opportunities, particularly in relation to minimally invasive techniques.…”
Section: Discussionmentioning
confidence: 99%
“…23 The British Association of Urological Surgeons' national registry results from 2016 to 2019 outlined that over 86% of radical prostatectomies in the UK were performed robotically, 24 and yet less than 30% of surgical trainees are gaining access to the required literacy and skill to deliver robotic surgery in their future consultant practice. 25,26 With the ability to record operations, and the development of laparoscopic and robotic technology, there is vast potential in our ability to better understand and measure how we train -if trainees are afforded access to these opportunities. In future, if done correctly, it is predicted that this may result in competence benchmarks or 'credentialing'.…”
Section: Unmet Needmentioning
confidence: 99%
“…Less than 30% of surgical trainees are gaining access to the required literacy and skill to deliver robotic surgery in their future consultant practice. 25,26 Having considered the evidence, the conclusions of the FOS:TEST Commission regarding trainee exposure to operating and how technology can enhance this are as follows.…”
Section: How Technology Partners Are Supporting Operating Skills Deve...mentioning
confidence: 99%
“…The results of a recent survey showed that although the robotic surgery training is considered important for the medical students [ 15 ], the majority of them did not had access to robotic surgery training in their hospital [ 16 ]. Trainees and residents still enter clinical robotic surgery practice without the necessary robotic skills and without having previous formal training on robotic surgery platform [ 6 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Skills acquisition is now related to the possibility to provide as early as possible robotic experience [ 5 , 17 ] within a relevant formal curriculum on robotic surgery training and to deliver appropriate documentation of the training quality and participants achievements [ 6 , [15] , [16] , [17] ]. One of the main conclusion drawn from studies is that training on simulators in isolation from traditional teaching methods contributes to the skills training of the surgeon, however the best time and place to use these skills comes only with experience [ 1 ].…”
Section: Introductionmentioning
confidence: 99%